SENGKETA LAUT CINA SELATAN DALAM PERSPEKTIF HUKUM INTERNASIONAL - Edmondus Sadesto Tandungan (Paulus Law Journal, 2020)
The South China Sea Region is one of the largest waters in the world and has a strategic role both in terms of economy, politics and security so as to make this region have great potential that can be utilized by countries around the region. The consequences of many interests in this region is potential conflict form many state. This article analyzes several disputes that occur in the South China Sea based on international law. The purpose of this article is to find out the steps taken by states to resolving these international legal disputes. Through the analysis in this article it was found that in the perspective of international law, the dispute over the South China Sea was sourced from differences of principles in determining maritime boundaries. The analysis of this article also found several steps and efforts that can be taken by the disputing countries to resolve the South China Sea dispute.Keywords : South China Sea; International Dispute; International Law